Effects of end products on fermentation profiles in Clostridium carboxidivorans P7 for syngas fermentation. (October 2016) - Zhang, Jie; Taylor, Steven; Wang, Yi
Highlights: Fermentation profiles in Clostridium carboxidivorans P7 strain was changed with addition of end-products. Acids re-assimilation is more favorable at 37 °C compared to 25 °C. Lower temperature facilitates carbon chain elongation. Redirection of carbon flow can be achieved by controlling the culture conditions. Abstract: Clostridium carboxidivorans P7 is a strict anaerobic bacterium capable of converting syngas to biofuels. However, its fermentation profiles is poorly understood. Here, various end-products, including acetic acid, butyric acid, hexanoic acid, ethanol and butanol were supplemented to evaluate their effects on fermentation profiles in C . carboxidivorans at two temperatures. At 37 °C, fatty acids addition likely led to more corresponding alcohols production. At 25 °C, C2 and C4 fatty acids supplementation resulted in more corresponding higher fatty acids, while supplemented hexanoic acid increased yields of C2 and C4 fatty acids and hexanol. Supplementation of ethanol or butanol caused increased production of C2 and C4 acids at both temperatures; however, long-chain alcohols were still more likely produced at lower temperature. In conclusion, fermentation profiles of C . carboxidivorans can be changed in respond to pre-added end-products and carbon flow may be redirected to desired products by controlling culture conditions.